Integrated Nutrient Management as a driving force for sustainable use of phosphorus - Pavinato, Paulo S.; Rosolem, Ciro A. [UNESP] (Elsevier, 2023)
Sustainable use of phosphorus (P) in agriculture has been in evidence lately both as an environmental risk and for the high fixation under tropical acidic soils. Integrated Nutrient Management (INM) has been shown to improve P-use efficiency (PUE) by allowing for reduced external inputs and avoiding loss from agricultural systems as well as fixation by soil colloids. Among the most promising INM actions for P conservation are (1) adjusting soil pH to increase P availability; (2) crop rotation/intercropping with P efficient species to use P from less available pools, and to increase soil organic matter to avoid P fixation; (3) crop breeding for adapted varieties to access more actively the soil P, improving traits such as root:shoot ratio, root morphology (more root hairs, cluster formation), exudation of organic compounds, and association of roots with mycorrhiza; (4) crop inoculation or association with P-solubilizing microorganisms; (5) use of modern P fertilizers, tuning fertilizer technologies to better synchronize solubilization with plant demand; (6) adoption of 4R nutrient stewardship to improve P fertilizer management; and (7) minimize or cease P loss by erosion/runoff in the production system. In this chapter we will explore more each of these topics for a more comprehensive understanding of how we should work to improve PUE in cropping systems.
Keywords: cropping system fertilization; cycling of nutrients; efficient P fertilizers; organic phosphorus; P adsorption; Phosphate sources; soil P target